2010
DOI: 10.1111/j.1467-6419.2009.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and Central Bank Independence: A Meta‐regression Analysis

Abstract: Using 59 studies, we perform a meta-regression analysis of studies examining the relationship between inflation and central bank independence (CBI). The studies considered are very different with respect to the CBI indicator used, the sample of countries and time periods covered, model specification, estimators used and publication outlet. We conclude that there is a significant publication bias. However, we also find a significant genuine effect of CBI on inflation. Differences between studies are not caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
83
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(86 citation statements)
references
References 65 publications
2
83
0
1
Order By: Relevance
“…13 This is consistent with the estimation result that a dummy variable for estimates of transition economies is not significant in the meta-regression model of Klomp and de Haan (2010), which takes the t value as a dependent variable (Table 4, p. 606). 14 More precisely, the dummy for the transition studies was insignificant in four of six models that take the PCC as a dependent variable and in all six models using the t value.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…13 This is consistent with the estimation result that a dummy variable for estimates of transition economies is not significant in the meta-regression model of Klomp and de Haan (2010), which takes the t value as a dependent variable (Table 4, p. 606). 14 More precisely, the dummy for the transition studies was insignificant in four of six models that take the PCC as a dependent variable and in all six models using the t value.…”
supporting
confidence: 77%
“…They include: Loungani and Sheets (1997), Maliszewski (2000), Cukierman et al (2002), Eijffinger and Stadhouders (2003), Hammermann and Flanagan (2007), Dumiter (2011), Maslowska (2011), Bogoev et al (2012a, Bogoev et al (2012b), and Petrevski et al (2012). Hereinafter, we will especially review studies after Dumiter (2011), which are not covered by Klomp and de Haan (2010).…”
Section: Central Bank Independence and Inflation: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we test for differences between developing and industrial countries. As noted, previous studies suggested that the legal indicator works best for industrial countries, while the TOR works best for developing countries (see Klomp and De Haan 2010 for further details). So, we replicated the last regression of Table 1 with developing countries only, while we replicated the last regression of Table 2 with OECD countries only.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Furthermore, studies based on the TOR suggest a positive relationship between this indicator of CBI and inflation in developing countries (see Klomp and De Haan 2010).…”
mentioning
confidence: 99%